New data on the pygmy grasshopper genus Epitettix Hancock, 1907 (Orthoptera: Tetrigidae) - Storozhenko, Sergey Yu. (Zootaxa, 2021)
The species composition of the genus Epitettix (Tetrigidae: Cladonotinae) is discussed. The differential diagnosis of the genus is given. New synonymies are proposed: Epitettix Hancock, 1907 = Vaotettix Podgornaja, 1986, syn. nov., = Pseudepitettix Zheng, 1995, syn. nov. Two new taxa are described, namely Epitettix mikhailovi sp. nov. from Vietnam (Gia Lai Province) and Epitettix punctatus montanus subsp. nov. from Malaysia (Sabah, North Borneo). Seven new combinations are established: Epitettix guibeiensis (Zheng et Jiang, 1995), comb. nov., E. hainanensis (Deng, 2020), comb. nov., E. linaoshanensis (Liang et Jiang, 2004), comb. nov., E. nigritibis (Zheng et Jiang, 2000), comb. nov., E. pimkarnae (Storozhenko et Dawwrueng, 2014), comb. nov., E. strictivertex (Deng, 2020), comb. nov., and E. parallelus (Podgornaja, 1986), comb. nov. The unknown male of the latter species is also described and illustrated.